Analytical analysis and simulation on fringe field effect of deflector plates applied in ultrafast electron microscopy. (November 2019) - Zhang, Lixin; Dong, Quanlin
Highlights: An Analytical model for the fringe field of deflector plates has been presented. The velocity dispersion, energy gain and stretched time are calculated. Single input deflector plates can induce sharp longitudinal velocity change. Deflector plates with double field input are recommended. Abstract: Deflector plates are one of the critical components in ultrafast electron microscope (UEM), which generates the short electron pulse. While the electron pulse can be stretched due to the velocity dispersion induced by the fringe field of the deflector plates, understanding the effect of the fringe field on the electron velocity and how to avoid the adverse effect of it are needed in the design of the deflector plates. In this paper, firstly, an analytical model of the fringe field of deflector plates with double field input is given. This analytical model can be adapted to other new designs with different double field inputs, and as an example, the velocity dispersion, stretched time, and energy gain of an electron pulse are calculated with a linear double field input. Secondly, three sets of particle tracing simulations on electron velocities have been studied in terms of different single field inputs. The simulated results show that the longitudinal velocity of the electron changes very differently as a result of the different voltage sign on the deflector plates. In our model, the longitudinal velocity is almost constant until the electron leaves the deflector plates. So the results suggest that the deflector plates with double field input are recommended not only in UEM setups but also in other charged particle beam setups where needs high deflection accuracy.